PENGARUH PEMBERIAN AMPAS TAHU TERHADAP PERTUMBUHAN IKAN LELE DUMBO (Clarias gariepinus) (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to determine the effect of giving tofu dregs on the growth of African catfish (Clarias gariepinus). This research was conducted in August - September 2021 at the Natural Laboratory of Biology Education FKIP Riau University. This study used a randomized block design consisting of 4 treatments with 3 replicate groups so that there were 12 experimental units. The object of this study was 120 tails of 4 weeks old African catfish. The treatment in this study consisted of control treatment, 15% tofu dregs treatment, 30% tofu dregs treatment, and 45% tofu dregs treatment. Collecting data by measuring the growth of absolute weight and water quality which is measured every 7 days for 4 weeks. The results showed that the highest absolute weight growth was found in the control treatment, which was 4.48g, but for the treatment the level of giving tofu dregs, 30% tofu dregs treatment was a good treatment compared to 15% tofu dregs and 45% tofu dregs with an absolute weight growth of 1, 66g. The results of the analysis of water quality showed a reasonable range for the life of African catfish (Clarias gariepinus) where the temperature ranged from 26o-30oC with a pH ranging from 5.47-6.67, and DO ranging from 4.20-4.94. Key Words: Growth, Clarias gariepinus, Tofu Dregs